Benchmarking: produtividade da mão de obra na execução de sistemas prediais hidráulicos e sanitários - Aidar, Gabriel Malvicino Nogueira Goulart (2022)
The management of labor productivity by civil construction companies has a great importance when considering the need to meet deadlines for the execution of services and, consequently, their maintenance in a competitive market, such as the construction industry. This work objective was to obtain indicators of labor productivity management in the execution of Hydraulic and Sanitary Building Systems based on primary data of labor productivity indicators (Daily, Cumulative and RUP(Cum-Pot)) obtained from bibliographies. The labor productivity management indicators called Disruption Index and Performance Ratio were calculated, as well as the establishment of benchmarking considering all the indicators involved for the tasks/subtasks inherent to the execution of the Hydraulic and Sanitary Building Systems. As a result, the following stand out: a) the excellent correlation between the Disruption Index (DI) and the Performance Ratio (PR), insofar as the higher this index, the worse the Performance Ratio, b) in relation to the Disruption Index, most of the subtasks were in the "Acceptable" Category; followed by the Category "Warning sign"; c) in relation to PR, it was observed that all tasks (two in total) in which kits were used in their execution had PR lower than the general PR. The main contribution of this work consisted in the establishment of indicators of labor productivity management, applied to Hydraulic and Sanitary Building Systems, whose procedure can be applied to other construction services.